Failure to adjust : how Americans got left behind in the global economy - Alden, Edward H. (Rowman & Littlefield, 2016)
Failure to Adjust presents an especially timely analysis of the trade policies of the Obama administration, and discusses how America can reassert itself as the leader in setting rules for international economic competition that would spread the benefits of global trade and investment more broadly.